RECONSTRUCTING THE ORIENT: A POSTCOLONIAL ANALYSIS OF AI-GENERATED ERASURE IN TRUMP'S GAZA VIDEO - Chemamat, Sakis; Sujiwa, Krisna; Prihatika, Yusrina Dinar (Rubikon : Journal of Transnational American Studies, 2025)
This study offers a critical analysis of an AI-generated video, circulated in early 2025, which depicts a fictional plan by former U.S. President Donald Trump to reconstruct Gaza as a hyper-modern, Westernized urban space. Through a postcolonial lens informed by Edward Said’s theory of Orientalism, this research examines how the video functions as a digital artifact that reproduces colonial power dynamics. The analysis reveals that the video—featuring luxury amenities, a monumental Trump statue, and the complete erasure of Palestinian people—constructs the West as a benevolent savior while symbolically eliminating indigenous presence and agency. Specific visual tropes, such as faceless children moving toward a futuristic city, the glorification of Trump as a heroic figure, and scenes of elite leisure, aestheticize systemic oppression and reframe military occupation as benign intervention. By converting trauma into spectacle and domination into development, the video exemplifies how AI-generated content can perpetuate Orientalist ideologies under the guise of satire or innovation. This research concludes that such digital representations are not politically neutral but actively reinforce imperial narratives, marginalize Palestinian voices, and normalize hierarchies of power. It underscores the urgency of critically engaging with emerging media technologies as sites of ideological reproduction in a post-9/11 world marked by enduring Islamophobia and digital Orientalism.